Religion, rationalism and civil war: The case of Algeria. Issue 4 (1st October 2020) - Isani, Mujtaba Ali
ABSTRACT: What role does religion play in understanding the outbreak of civil war? The purpose of this study is to offer an alternative understanding which conceptualises religion as discourse, religious identity as sacred narrative, and religious nationalism as a conflict over the power to shape interpretations of political legitimacy. A rationalist explanation for the role of religion in the outbreak of the Algerian civil war provides an empirical motivation for the argument. By conceptualising religion largely in rational-material terms, I contend that rationalists fail to appreciate religion's unique attraction – the belief that the ultimate seat of political authority exists beyond the state and in some transcendent reality. As an alternative, I conceptualise religion as a discursive institution, explaining how the contest to shape a faith's sacred narrative can result in physical violence. This exercise is a first step in a broader research agenda addressing how a robust theory of religious identity can enhance scholars' understanding of peace and conflict.